2009
DOI: 10.1016/s1567-5688(09)70541-0
|View full text |Cite
|
Sign up to set email alerts
|

Abstract: P246 CCN3 INHIBITS NEOINTIMAL HYPERPLASIA THROUGH MODULATION OF SMOOTH MUSCLE CELL GROWTH AND MIGRATION

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Top differentially expressed genes within the ascending SMC population includes expected developmental genes such as Tbx20 and Hand2 , but also numerous genes with previously demonstrated roles in atherosclerosis suggesting vascular bed specific disease risk mechanisms (Figure 2I, Supplemental Table 2). These genes include Ccn3 (cellular communication network factor 3) which has previously reported vascular protective effects by inhibiting neointimal formation and plaque development; 34, 35 Dcn (decorin), which has been shown to be protective in atherosclerosis; 36 Col14a1 (collagen type XIV alpha 1 chain) which has increased expression in human atherosclerotic plaque; 37 and Tns1 (tensin 1) a previously identified CAD GWAS gene. 38 Notably, we identify specific vascular development and inflammation genes as having higher expression within SMCs isolated from the carotid artery, such as Junb (junb proto-oncogene) (Figure 2J, Supplemental Table 3), Atf3 (activating transcription factor 3), and Egr1 (early growth response 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Top differentially expressed genes within the ascending SMC population includes expected developmental genes such as Tbx20 and Hand2 , but also numerous genes with previously demonstrated roles in atherosclerosis suggesting vascular bed specific disease risk mechanisms (Figure 2I, Supplemental Table 2). These genes include Ccn3 (cellular communication network factor 3) which has previously reported vascular protective effects by inhibiting neointimal formation and plaque development; 34, 35 Dcn (decorin), which has been shown to be protective in atherosclerosis; 36 Col14a1 (collagen type XIV alpha 1 chain) which has increased expression in human atherosclerotic plaque; 37 and Tns1 (tensin 1) a previously identified CAD GWAS gene. 38 Notably, we identify specific vascular development and inflammation genes as having higher expression within SMCs isolated from the carotid artery, such as Junb (junb proto-oncogene) (Figure 2J, Supplemental Table 3), Atf3 (activating transcription factor 3), and Egr1 (early growth response 1).…”
Section: Resultsmentioning
confidence: 99%
“…Prior experimental work has shown that Ccn3 inhibits neointima formation through inhibition of vascular smooth muscle proliferation and regulation of macrophage foam cell formation, while overexpression of Ccn3 inhibits vascular inflammation and is protective against atherosclerosis in mice. 34, 35, 85 Given the differential expression of Ccn3 between vascular beds, one hypothesis may be that this Ccn3 pathway plays differing roles in mediating disease across vascular beds. Perhaps this suggests that augmenting this pathway may prove to have a greater benefit in vascular beds which are ‘deficient’ in Ccn3 , i.e.…”
Section: Discussionmentioning
confidence: 99%
“…CCN3 is involved in myogenesis, affecting the formation and stabilization of attachment structures that transmit force from the muscle to tendon (Lafont et al, 2005). In contrast, Ccn3-deficient mice develop normally until adulthood and both males and females can reproduce (Shimoyama et al, 2010). Similarly, Ccn3 mutant mice deficient in the VWC domain displayed good health, albeit with mild skeletal defects (Heath et al, 2008).…”
Section: The Expression Pattern Of Ccn2 During Development Ismentioning
confidence: 99%